Breakfast Consumption Is Positively Associated with Usual Nutrient Intakes among Food Pantry Clients Living in Rural Communities. Issue 3 (9th November 2019) - Liu, Yibin; Tooze, Janet A; Zhang, Yumin; Leidy, Heather J; Bailey, Regan L; Wright, Breanne; Ma, Mengran; Stluka, Suzanne; Remley, Dan T; McCormack, Lacey A; Franzen-Castle, Lisa; Henne, Rebecca; et al.
ABSTRACT: Background: Breakfast consumption has declined over the past 40 y and is inversely associated with obesity-related diet and health outcomes. The breakfast pattern of food pantry clients and its association with diet is unknown. Objective: The objective is to investigate the association of breakfast consumption with diet quality and usual nutrient intakes among food pantry clients ( n = 472) living in rural communities. Methods: This was an observational study using cross-sectional analyses. English-speaking participants ≥18 y (or ≥19 y in Nebraska) were recruited from 24 food pantries in rural high-poverty counties in Indiana, Michigan, Missouri, Nebraska, Ohio, and South Dakota. Participants were surveyed at the pantry regarding characteristics and diet using 24-h recall. A second recall was self-completed or completed via assisted phone call within 2 wk of the pantry visit. Participants were classified as breakfast skippers when neither recall reported breakfast ≥230 kcal consumed between 04:00 and 10:00; breakfast consumers were all other participants. The Healthy Eating Index-2010 was modeled with breakfast pattern using multiple linear regression. Mean usual intake of 16 nutrients was estimated using the National Cancer Institute Method and compared across breakfast pattern groups. Usual nutrient intake was compared with the Estimated Average Requirement (EAR) or Adequate Intake (AI) to estimate the proportion of population not meeting the EAR or exceeding the AI. Results: A total of 56% of participants consumed breakfast. Compared with breakfast skippers, breakfast consumers had 10–59% significantly higher usual mean intakes of all nutrients ( P ≤ 0.05), and had 12–21% lower prevalence of at-risk nutrient intakes except for vitamin D, vitamin E, and magnesium. Conclusions: Adult food pantry clients living in rural communities experienced hardships in meeting dietary recommendations. Breakfast consumption was positively associated with usual nutrient intakes in this population. This trial was registered at clinicaltrials.gov as NCT03566095.